MATHEMATICS TOOLS DEVELOPMENT BASED ON WEB WITH MOODLE APPLICATIONS IN BASED STATISTICS SUBJECT - Bagus Ardi S, Rina Dwi S Febrian Dewanto (PHENOMENON, 2014)
ABSTRACTThis research is the development of learning tools, which aims to: (1)describe the development of tools and produce mathematics learning applicationbased on WEB with MOODLE Application On valid Based StatisticsSubject. (2) To determine Effectiveley results the tools of learning.Moreover, the learning tools to be developed are the whole Syllabus, lessonplans, and text book learning. Those tools are developed by using the developmentmodel of 4D thiagdarajan Field trials conducted an web learningcourse on Education Statistics experiments Class, in this study were36 students at class 3A, while the control class is 35 students of 3B class.Independent variables are motivation and activity, while the dependentvariable is the learning achievement. Data taken with the deployment ofquestionnaires, observation and tests. Data processed with comparisons ttest and regression.The results the influence of motivation and activity of learningachievement of 89.7% d) and the average of learning achievement experimentalclass achieve exhaustiveness 74.25 e) Average learning achievementof experimental class 74.25, better than average learning achievement forcontrol class 64.57. Based on the research results obtained are valid learningtools and effective learning that show the development of learningtools goals achieved.Keywords: Development Learning Tools, WEB, MOODLE